PENGARUH STRES KERJA DAN CYBERLOAFING TERHADAP KINERJA KARYAWAN PT. PERKEBUNAN NUSANTARA V SEI BUATAN KABUPATEN SIAK PROVINSI RIAU - Wijayant Tanti Achmat; Hendriani Susi; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of work stress and cyberloafing on the performance of employees of PT. Perkebunan Nusantara V Sei Buatan. The population in this study includes all employees of the financial administration and HR/General administration at the PT. Perkebunan Nusantara V Sei Buatan, totaling 37 people. Primary data were collected using a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using multiple linear regression analysis with the help of the SPSS program. The sampling technique that has been selected is the saturated sampling technique (37 employees at PT. Perkebunan Nusantara V Sei Buatan). The results showed that: 1) there was a significant effect and cyberloafing on the performance of employees of PT. Perkebunan Nusantara V Sei Buatan, 2) there is a negative and significant influence of work stress on the performance of employees of PT. Perkebunan Nusantara V Sei Buatan, 3) there is a negative and significant influence of cyberloafing on the performance of employees of PT. Perkebunan Nusantara V Sei BuatanKeywords : Job Stress, Cyberloafing, Employee Performance.